Is high vitamin B12 status a cause of lung cancer?. Issue 6 (15th January 2019) - Fanidi, Anouar; Carreras‐Torres, Robert; Larose, Tricia L.; Yuan, Jian‐Min; Stevens, Victoria L.; Weinstein, Stephanie J.; Albanes, Demetrius; Prentice, Ross; Pettinger, Mary; Cai, Qiuyin; Blot, William J.; Arslan, Alan A.; et al.
Abstract : Vitamin B supplementation can have side effects for human health, including cancer risk. We aimed to elucidate the role of vitamin B12 in lung cancer etiology via direct measurements of pre‐diagnostic circulating vitamin B12 concentrations in a nested case–control study, complemented with a Mendelian randomization (MR) approach in an independent case–control sample. We used pre‐diagnostic biomarker data from 5183 case–control pairs nested within 20 prospective cohorts, and genetic data from 29, 266 cases and 56, 450 controls. Exposures included directly measured circulating vitamin B12 in pre‐diagnostic blood samples from the nested case–control study, and 8 single nucleotide polymorphisms associated with vitamin B12 concentrations in the MR study. Our main outcome of interest was increased risk for lung cancer, overall and by histological subtype, per increase in circulating vitamin B12 concentrations. We found circulating vitamin B12 to be positively associated with overall lung cancer risk in a dose response fashion (odds ratio for a doubling in B12 [ORlog2B12 ] = 1.15, 95% confidence interval (95%CI) = 1.06–1.25). The MR analysis based on 8 genetic variants also indicated that genetically determined higher vitamin B12 concentrations were positively associated with overall lung cancer risk (OR per 150 pmol/L standard deviation increase in B12 [ORSD ] = 1.08, 95%CI = 1.00–1.16). Considering the consistency of these two independent and complementary analyses, these findings support the hypothesis that high vitamin B12 status increases the risk of lung cancer. Abstract : What's new? Several B‐complex vitamins have been linked to cancer risk. In this study, high serum levels of vitamin B12 were associated with an increased risk of lung cancer. The authors first ran a nested case‐control study, then confirmed their findings using a Mendelian randomization approach based on genetic data from a much larger database including both lung‐cancer patients and controls. The authors conclude that these findings support the hypothesis that high circulating vitamin B12 concentrations increase the risk of lung cancer.